Behavioral and Neural Arguments of Motivational Influence on Decision Making During Uncertainty - Giustiniani, Julie; Nicolier, Magali; Teti Mayer, Juliana; Chabin, Thibault; Masse, Caroline; Galmès, Nathan; Pazart, Lionel; Trojak, Benoit; Bennabi, Djamila; Vandel, Pierre; Haffen, Emmanuel; Gabriel, Damien (Frontiers in Neuroscience, 2020)
The scientific world is increasingly interested in motivation, primarily due to the suspected impact on decision-making abilities, particularly in uncertain conditions. To explore this plausible relationship, 28 healthy participants were included in the study and performed decision-making and motivational tasks while their neural activity was recorded. All participants performed the Iowa Gambling Task (IGT) and were split into two groups based on their score; one favorable group with 14 participants who performed advantageously and one undecided group with 14 participants who failed to develop the correct strategy on the IGT. In addition, all participants performed the Effort Expenditure for Reward Task (EEfRT), which defines the motivational level of each participant. The completion of both tasks allowed for the exploration of the relationship between the motivational level and decision-making abilities. Both tasks were adapted to allow for electroencephalography (EEG) recordings to study the neural bases of events associated with decision making behavior and reward processing. Behavioral results showed no difference in EEfRT performances on the whole task between the two groups' performances on the IGT. However, there was a negative correlation between the difficulty to develop an optimal strategy on the IGT and the percentage of difficult choices at the 90% condition on the EEfRT. This behavioral result leads to the hypothesis that reward sensitivity may induce an inability to develop an optimal strategy on the IGT. Group analysis demonstrated that only the undecided group showed a P300, whereas the favorable group showed a blunted P300. Similarly, on the whole group analysis, there was a negative correlation between the P300 amplitude and the ability to develop an optimal strategy on the IGT. In conclusion, behavioral and neuronal data provides evidence that the propensity to focus only on the immediate outcomes leads to the development of an inefficient strategy on the IGT, without influence of motivation.